1997
DOI: 10.3989/gya.1997.v48.i1.763
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fatty acid composition on the formation of polar glycerides and polar fatty acids in sunflower oils heated at frying temperatures.

Abstract: RESUMENInfluencia de la composición de ácidos grasos en la formación de glicéridos polares y ácidos grasos polares en aceites de girasol calentados a temperaturas de fritura.Aceites de girasol convencional y alto oleico así como una mezcla al 50% de ambos fueron calentados a diferentes temperaturas bajo condiciones controladas. Se cuantificaron los compuestos polares totales, los grupos principales de glicéridos, áci-dos grasos polares totales, los grupos principales de ácidos grasos polares y la pérdida de ác… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…During frying, polyunsaturated fatty acids (PUFA) were decreased and saturated fatty acids (SFA) were increased. It was reported that heat treatment of fats induces modifications of fatty acids with two or three double bonds [19,20]. In our study the level of PUFA tended to decrease, whereas that of SFA increased.…”
Section: Resultsmentioning
confidence: 42%
“…During frying, polyunsaturated fatty acids (PUFA) were decreased and saturated fatty acids (SFA) were increased. It was reported that heat treatment of fats induces modifications of fatty acids with two or three double bonds [19,20]. In our study the level of PUFA tended to decrease, whereas that of SFA increased.…”
Section: Resultsmentioning
confidence: 42%
“…Arroyo et al. (1995) and Jorge et al. (1997) pointed out that heat treatment of fats induces modifications of fatty acids with two or three double bonds.…”
Section: Resultsmentioning
confidence: 99%
“…It was then suggested that linoleate could be the primary reactant but the oxidation reactions could propagate readily to all unsaturated species. A study on the formation of polar compounds at frying temperatures [8], indicated that linoleate was preferentially involved in the formation of TAG polymers, although the participation of oleate became very important at low linoleate content.…”
Section: Introductionmentioning
confidence: 99%